Recent sex work and associations with psychosocial outcomes among women living with HIV: findings from a longitudinal Canadian cohort study. Issue 3 (22nd March 2022) - Logie, Carmen H.; Sokolovic, Nina; Kazemi, Mina; Smith, Stephanie; Islam, Shaz; Lee, Melanie; Gormley, Rebecca; Kaida, Angela; de Pokomandy, Alexandra; Loutfy, Mona; ,
Abstract: Introduction: Sex workers are disproportionately impacted by the HIV pandemic across global contexts, in part due to social and structural contexts of stigma and criminalization. Among women living with HIV, there is a dearth of longitudinal information regarding dynamics of sex work engagement and associated social and health outcomes. In order to better understand the social contexts and health needs of sex working women living with HIV, this study aimed to understand recent sex work prevalence and its longitudinal associations with stigma, psychosocial and clinical HIV outcomes among women living with HIV in Canada. Methods: We conducted a three‐wave prospective cohort survey at 18‐month intervals with women living with HIV aged 16 and older in three Canadian provinces between 2013 and 2018. We used generalized estimating equations to examine longitudinal associations between recent (past 6‐month) sex work with three types of outcomes: psychosocial (recent violence, recent injection drug use, hazardous alcohol use, clinical depression and post‐traumatic stress disorder), clinical HIV (CD4 count and viral load) and stigma (HIV‐related stigma, racial discrimination and gender discrimination). Equations were adjusted for socio‐demographic factors associated with sex work across all three waves: province, age, income, gender identity, sexual orientation, education level, ethnicity and housing security. Results and Discussion: Of 1422 participants, 129 (9.1%) reported recent sex work during at least one wave (82 at baseline, 73 at first follow‐up and 32 at second follow‐up). In adjusted analyses, recent sex work was associated with psychosocial outcomes, including: past 3‐month violence (adjusted odds ratio [AOR] = 2.47, 95% CI = 1.70, 3.60), past 6‐month injection drug use (AOR = 3.49, 95% CI = 2.21–5.52), hazardous alcohol use (AOR = 2.00, 95% CI = 1.04–3.89) and depression (AOR = 1.51, 95% CI = 1.06–2.15). In unadjusted analyses, sex work was also associated with clinical HIV outcomes and gender discrimination, but not racial discrimination/HIV‐related stigma. Conclusions: Among women living with HIV in Canada, sex work engagement is dynamic, and sex workers are more likely to report recent violence, recent injection drug use, problematic alcohol use and clinical depression. Violence prevention and support, harm reduction, mental health promotion and sex work‐affirming programs could be employed to optimize health and rights for sex working women living with HIV.